Pengaruh Karakteristik Sumber Daya Manusia Pada Efektivitas SIMAK BMN - Satiari, Ni Putu Ayu Ista; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 30 No 3 (2020)DO - 10.24843/EJA.2020.v30.i03.p12, 2020)
The purpose of this study was to determine the effect of human resource characteristics on the effectiveness of SIMAK BMN. This research was conducted in the Denpasar KPKNL work unit. The number of samples used was 118 work units with non-probability sampling method, namely saturated sampling technique. The analysis technique used is multiple linear analysis. Based on the results of research conducted stated that the level of education, training, experience and motivation has a positive effect on the effectiveness of SIMAK BMN. This means that the high perception of SIMAK BMN operators regarding the educational benefits received is higher with training material that is fun, easy to understand and apply and the more experience the operator has and the higher the motivation of the operator, the effectiveness of SIMAK BMN increases. Keywords: Level Of Education; Training; Experience; Motivation, Effectiveness Of SIMAK BMN.